(untitled) (Canadian Oncology Today, 2025)
Small cell lung cancer is an aggressive cancer with a poor prognosis. New treatment paradigms have developed with the incorporation of new therapies in the last few years, aiming to improve patient survival. Some emerging therapies include the addition of immunotherapy to chemotherapy. This article provides a practical review of the current and upcoming treatment options for SCLC in both limited and extensive stages, focusing on integrating radiation and immunotherapy.